The Test and Training Enabling Architecture (TENA) Supporting the Decentralized Development of Distributed Applications and LVC Simulations - Noseworthy, J.R. (2008 12th IEEE/ACM International Symposium on Distributed Simulation and Real-Time Applications, 2008)
The test and training enabling architecture (TENA) supports the rapid, reliable, decentralized and collaborative development of applications for large-scale, high-performance, distributed, real-time and embedded systems.The U.S. Department of Defense (DoD) uses TENA for distributed testing and training, combining the use of real sensor systems with data from virtual and constructive simulations. Such systems are called live, virtual and constructive (LVC) systems. The resulting data must be exchanged in real-time with high performance. Most of the simulations and sensors are inherently distributed, typically over a large geographic area. The developers working to support the ranges are themselves geographically distributed, may never have met each other, and do not report to a common authority. Nevertheless, these developers must collaborate to execute a joint testing or training event. At the core of TENA, the TENA middleware delicately weaves together a unique combination of model-driven, code-generated software with high-level, easy-to-understand programming abstractions and an API designed to detect programming errors at compile-time rather than run-time, where the cost of an error could be extremely high. TENA provides re-usable standardized components to simplify the development of TENA applications. TENA features a flexible and extensible TENA object model compiler (OMC) which can automatically generate example programs, test programs, and gateways to legacy systems with older, less sophisticated software architectures such as distributed interactive simulation (DIS) and the high-level architecture run-time infrastructure (HLA/RTI). More than 4,000 registered users currently utilize TENA at dozens of facilities worldwide. TENA supports numerous major test and training events. For more information, see https://www.tena-sda.org/.